Two-step Newton methods - Magreñán, Á. Alberto; Argyros, Ioannis K (Contemporary study of iterative methods: convergence, dynamics and applications, 2021)
In this chapter we extend the applicability of two-step Newton's method for solving nonlinear equations.
Capítulo del libro "Contemporary study of iterative methods: convergence, dynamics and applications"
Keywords: two-step Newton's method; banach space; convergence; WOS(2)